2018
DOI: 10.1080/14760584.2018.1471987
|View full text |Cite
|
Sign up to set email alerts
|

How to evaluate potential non-specific effects of vaccines: the quest for randomized trials or time for triangulation?

Abstract: Emerging evidence suggests that vaccines, in addition to their disease-specific effects, have important non-specific effects (NSEs), which contribute to their overall effect on mortality and morbidity. Immunological studies have shown that NSEs are biologically plausible. Many advocate that randomized controlled trials (RCTs) with overall mortality or morbidity as the outcome are the only way forward to confirm or refute NSEs. Areas covered: We discuss the limitations of using RCTs only as a tool to evaluate N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 66 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Hopefully, the interest will not disappear this time. There are huge potentials in studying systematically -in RCTs, in natural experiments, and in observational studies -the NSEs of different vaccines in different disease environment and with different interacting interventions with a view to further improve overall health and not just specific-disease immunity (31).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Hopefully, the interest will not disappear this time. There are huge potentials in studying systematically -in RCTs, in natural experiments, and in observational studies -the NSEs of different vaccines in different disease environment and with different interacting interventions with a view to further improve overall health and not just specific-disease immunity (31).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…The protocol has several strengths, compared to similar studies. First, it aligns with the current increasing consensus on the importance of mixed methods [ 32 ] and of triangulation approaches in accruing robust evidence in the evaluation of interventions [ 33 - 35 ]. Two aspects of community trials call for triangulation approaches.…”
Section: Discussionmentioning
confidence: 66%
“…1 The published medical literature is filled with examples of associations between treatment and outcome identified in observational studies that were subsequently disproven by well conducted random ised controlled trials (RCTs). [2][3][4] Framed this way, findings from an analysis of cardiovascular guidelines, 5 which showed that less than 10% of American College of Cardiology and American Heart Association and less than 15% of European Society of Cardiology guideline recommendations were based on evidence from RCTs, should be concerning for anyone involved in clinical research or clinical care. Without evidence from RCTs, physicians are forced to base clinical decisions on flawed inference from clinical outcome data or simply rely on expert opinion.…”
Section: High-quality Evidence To Inform Clinical Practicementioning
confidence: 99%
“…But the experience of the past decade has shown that smaller efforts will not be adequate. studies have suggested different thresholds of an RR of 10 or higher, 2 or 5 or higher (or RR <0•2) 3 to avoid an RCT. We agree that larger effects are less likely to be explained by confounding factors, but regulatory agencies appear to have no explicit or implicit thresholds for approval without requiring further testing in RCTs.…”
Section: High-quality Evidence To Inform Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation